Martin Luther his challenge then and now - Lyons, P. Fintan (Columba Press, 2017)
"A study of the phenomenon of Luther, and his effects on church and society, leads in the end to recognising that issues which existed then are endemic to Christianity in every century. Luther said he would use his power as a baptised Christian to excommunicate the pope and cardinals if the Bull of condemnation against him proved genuine (which he knew it was), could there be any common ground between him and the papal church then or now?"...Publisher description